Is Informality Good for Business? The Impacts of IDP Inflows on Formal Firms - Rozo, Sandra; Winkler, Hernan (World Bank, Washington, DC, 2019)
This paper examines the effects of large inflows of internally displaced persons (IDP), who are primarily absorbed by the informal sector, on the behavior of formal manufacturing firms in Colombia. To identify causal effects, the analysis employs annual, firm-level panel data between 1995 and 2010 and exploits that when conflict intensifies, forcefully displaced individuals tend to migrate to municipalities where people from their origin locations settled earlier. The paper finds that large inflows of IDP induce sizable, negative effects on the intensive and extensive margins of production of formal firms. These effects are stronger for firms operating in sectors that face a stronger competition from the informal economy.